Suture Anchor Repair of Avulsed Adductor Pollicis Injury, Secondary to Motor Vehicle Collision: Case Report and Technique. Issue 2 (June 2019) - Wait, Eric; Suryavanshi, Joash R.; MacKay, Brendan J.
Abstract : The thenar eminence of the thumb is made up of 4 intrinsic muscles: abductor pollicis brevis, opponens pollicis, flexor pollicis brevis, and the adductor pollicis (ADD). While both heads of the ADD insert on the medial base of the thumb proximal phalanx, the oblique head originates on the capitate and second and third metacarpals, and the transverse head originates on the distal half of the third metacarpal. We present the case of a 36-year-old man who was involved in a motor vehicle collision and sustained a laceration in the first webspace with 1 cm extrusion of the ADD and no neurovascular deficiencies on examination. X-ray imaging noted no bony abnormalities. The only identifiable injury was to the ADD muscle which was avulsed from its origin and was extruded through the open wound in the first webspace. A double-row running locking 3-0 fiberwire suture technique was used to have a solid anchor point with which to secure the muscle to its origin. It was secured to the second metacarpal with Mitek mini suture anchors that was sutured on the opposing side of the double-row fiberwire suture and anchored to the second metacarpal proximally and distally in the metacarpal. We report good clinical outcomes postoperative, with intact range of motion and no surgical complication at the 6-month follow-up visit. The patient has ongoing physical therapy to reduce any residual strength deficits.